2021
DOI: 10.1007/s11418-021-01484-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploration for the real causative agents of licorice-induced pseudoaldosteronism

Abstract: I investigated the causative agents of licorice-induced pseudoaldosteronism, which is a frequent side effect of Japanese traditional Kampo medicines. Glycyrrhizin (GL), the main ingredient of licorice, is absorbed after being metabolized to glycyrrhetinic acid (GA) by intestinal bacteria, and then metabolized in liver to 3-monoglucuronyl-glycyrrhetinic acid (3MGA). In normal condition, 3MGA is excreted into bile via a multidrug resistance-related protein (Mrp) 2, therefore, 3MGA does not appear in blood circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A proinflammatory effect of aldosterone has been described in several tissues [ 41 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ], including capillary endothelium [ 94 ]. Aldosterone acts synergistically at the innate immunity receptor, TLR4, with the TLR4 ligand lipopolysaccharide (LPS) to induce depression-like behavior [ 95 ]; therefore, the combined action of Glycyrrhiza glabra to reduce the RAAS [ 21 , 22 , 23 , 24 ] and antagonize the TLR4 receptor acts synergistically to reduce inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A proinflammatory effect of aldosterone has been described in several tissues [ 41 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ], including capillary endothelium [ 94 ]. Aldosterone acts synergistically at the innate immunity receptor, TLR4, with the TLR4 ligand lipopolysaccharide (LPS) to induce depression-like behavior [ 95 ]; therefore, the combined action of Glycyrrhiza glabra to reduce the RAAS [ 21 , 22 , 23 , 24 ] and antagonize the TLR4 receptor acts synergistically to reduce inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the 11β-HSD2 inhibitors is glycyrrhizin, an active component of licorice ( Glycyrrhiza glabra ). Inhibition of 11β-HSD2 results in a reduction in RAAS activity and an increase in blood pressure in animal models [ 21 , 22 ] and humans [ 21 , 23 , 24 ]. Treatment with glycyrrhizin induced antidepressant effects in two small studies in depressed patients [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicated that glycyrrhizin, the chief component of Glycyrrhiza, and its metabolites cause pseudoaldosteronism by suppressing 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) in renal distal tubular epithelial cells [ 13 , 24 ]. We identified concomitant hypertension as an independent factor linked to Kampo formula-induced pseudoaldosteronism.…”
Section: Discussionmentioning
confidence: 99%
“…type 2 (11β-HSD2) in renal distal tubular epithelial cells [13,24]. We identified concomitant hypertension as an independent factor linked to Kampo formula-induced pseudoaldosteronism.…”
Section: Plos Onementioning
confidence: 94%
“…Evidence of the efficacy and safety of Kampo medicines for refractory symptoms in patients with cancer, such as anorexia, 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 fatigue, 11 and peripheral neuropathy, 12 , 13 , 14 , 15 , 16 , 17 , 18 has been accumulated. Adverse reactions to Kampo medicines are well documented, such as hepatic dysfunction, interstitial pneumonia, and pseudoaldosteronism, 19 , 20 , 21 , 22 but the incidence of these adverse reactions is extremely low. The long-term history of well-described Kampo combinations over hundreds of years, controlled quality of Kampo medicines, education of the doctors, and the small quantity of the individual herbal drug allow a safe-use of Kampo medicines alongside chemotherapy.…”
Section: Introductionmentioning
confidence: 99%